Refleksi Masyarakat Indonesia Masa Kini Melalui Cerpen Terbitan Kompas: Social reflection of contemporary Indonesian society through short stories published by Kompas - Ulwatunnisa, Marwah (Journal of Literature and Education, 2023)
This research aims to describe the social reflection of today's society through literary works, namely short stories. This research uses a sociological study of literature by Alan Swingewood. This type of research is descriptive qualitative. The data source used is three short stories from the Kompas newspaper: Istri Sempurna by Rahardi Handining, Drs. Mandaram by Harris Effendi Thahar, and Tamu Istimewa by Dahri Dahlan. The results of this research are a social reflection of contemporary Indonesian society, namely regarding the description of divorce cases, the emergence of gynoids that influence human life and relationships, veganism as a representation of changes in people's mindset towards healthy lifestyles, customary norms (folkways) that are still carried out, namely visiting and entertaining, to the practice of bribery which has spread to various groups and various sectors, one of which is the education sector.